2009
DOI: 10.1002/jsfa.3711
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant content of edible sprouts: effects of environmental shocks

Abstract: BACKGROUND: Edible sprouts are thought to be rich in health-promoting phytochemicals that are known to prevent a number of chronic and degenerative diseases. In mature plants, environmental shocks have been used to enhance health-promoting phytochemicals. The primary objective of this study was to use environmental shocks involving high light and chilling in sprouts of alfalfa, broccoli and radish to improve their phenolic composition.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 34 publications
(44 reference statements)
1
27
0
1
Order By: Relevance
“…Inhibition of elongation in tested microgreens was observed under higher irradiance levels: hypocotyls of mustard (P=0. 27 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of elongation in tested microgreens was observed under higher irradiance levels: hypocotyls of mustard (P=0. 27 (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…We suggest that higher, 220-330 µmol m -2 s -1 PPFD levels should be used by growers seeking normal growth and superior nutritional quality of brassica microgreens. It has been previously reported that high light (>400 μmol m -2 s -1 ) treatment, as a mild environmental stress, was useful in enhancing nutritional properties in sprouts [27] and mature plants [15,28]. Plants typically respond to environmental stressors by inducing antioxidant production as a defense mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of sprouting temperature on the concentration of bioactive compounds during germination of soybeans demonstrated that optimal increases in the concentrations of isoflavone aglycones (daidzein and genistein) and saponin glycosides were observed with germination at 30 °C (Paucar‐Menacho et al ., ). In the studies of Oh & Rajeshekar (), chilling and high light intensity during the growth of radishes and alfalfa sprouts caused qualitative and quantitative changes in phenolic profiles and antioxidant activities.…”
Section: Resultsmentioning
confidence: 99%
“…Sprouting is reported to be associated with improvements of nutritional value of seeds, since it promotes accumulation of health-promoting phytochemicals (phenolic acids, flavonoids, and vitamins) (Oh and Rajashekar, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is well acknowledged that plants under various abiotic stresses (i.e. drought, salinity, high light and chilling; Lim et al 2012;Oh and Rajashekar, 2009) accumulate several phytochemicals, which play a major role in the adaptation of plants to unfavourable growing conditions (Guo et al, 2014;Yuan et al, 2010). Quality traits, as well as the level and activity of bioactive compounds occurring in foods of plant origin may be modified using a range of biotechnological and agronomic practices.…”
Section: Introductionmentioning
confidence: 99%